Ambiente de jogos educacionais de adivinhação baseados no conhecimento de senso comum - Ferreira, Alexandre Mello (2008)
The use of computer games for education is getting more and more common, since they are considered a potential tool for facilitating the learning process, making it more comfortable and natural for students. However, the majority of the existent educational games neither allows content personalization nor offers any support for teachers to contextualize the game content to the socio-cultural reality of a certain group of students. The environment What is it? developed in this project allows teachers to co-author card-based quiz games and offers common sense support from a common sense knowledge base previously filtered by teachers, according to the desired student profile, making possible fit the content for the students needs. The environment is divided into three modules: (I) the editor s module, where teachers can create a game instance; (II) learner s module which is used by players to guess the secret word of a game card (for instance, AIDS), which is related to a topic (STD Sexually Transmitted Disease, for example) that is referred to one of the transversal themes proposed by SEF/MEC (for example, Sexual Education), inferring the word from the clues that are presented one by one; and (III) the evaluation module for teachers to analyze the performance of each student in playing the game and to make their conclusions. The environment also proposes a new way for collecting common sense knowledge through which mechanisms on the editor s and player s modules store all the interaction of teachers and students with the system, mapping the data gotten from the interaction in relations stored in the Open Mind Common Sense (OMCS-Br) knowledge base, which currently collects common sense knowledge in the form of natural language statements through voluntary contributions in the site of the project (http://www.sensocomum.ufscar.br). For assessing the environment, a case study was performed in two state schools one in São Carlos/SP and another in Foz do Iguaçu/PR that allowed to certify the interest of teachers and students in using this kind of educational tool and to collect opinions from teachers about using common sense knowledge for contextualizing the generated content. Moreover the potential for collecting new common sense statements through the game, contributing towards making the OMCS-Br common sense knowledge base grow faster, is demonstrated.